تعثر المشروعات الصغيرة وأثره على الأداء المصرفي في ظل إعادة الإعمار في سورية - ديوب، محمد معن; ديك، رولى (جامعة تشرين, 2018)
تحتل المشروعات الصغيرة في الوقت الراهن أهمية خاصة في فترة الأزمة في سورية لدورها في الاقتصاد المحلي وتغطية السوق بالبضائع المحلية الصنع. تعتبر المشاريع الصغيرة أحد مصادر الدخل الرئيسية والتي تساهم في تحسين الوضع الاقتصادي والاجتماعي لفئة كبيرة من السكان في سورية. كما أن فشل هذه المشاريع وتعثرها له انعكاسات كبيرة وعلى قطاعات مختلفة وأهمها القطاع المصرفي. يهدف البحث إلى دراسة تعثر المشروعات الصغيرة في ظل الأزمة السورية وانعكاسه على الأداء المصرفي في سورية. كما يهدف البحث إلى تقديم الحلول المقترحة لتمويل القروض للمشروعات الصغيرة في فترة إعادة الإعمار. اعتمد البحث بشكل أساسي على المنهج الوصفي التحليلي الذي يعتمد على وصف ظاهرة تعثر المشروعات الصغيرة. يقوم هذا البحث بدراسة ميدانية لثلاث مصارف حكومية سورية. توصلت الدراسة إلى تعثر قروض التمويل الصغير في المصارف وتوقفت كليا بسبب بداية الأزمة وتعثر الديون للمقترضين. كما فاقت المبالغ المترتبة من فوائد وغرامات تأخير للقروض قيمة القرض المتعثر بمقدار 40% تقريبا من مبلغه. أما نسب الربحية في هذه المصارف فتأثرت بشكل واضح بالأزمة السورية من جهة وبتعثر القروض في عام 2011 بنسبة كبيرة جدا. أن التحليل المالي والمحاسبة تتطلب اتخاذ قرارات حاسمة بأن منح هذه القروض في المصارف الحكومية وتقليل المخاطر الائتمانية المترتبة على هذه البنوك يساهم في مرحلة إعادة الإعمار. وقد توصلت الدراسة إلى نتائج أهمها بأن المصارف الحكومية لها خصائص وتلعب دورا في تشكيل سياسات الاستثمار والتشغيل في الشركات وتستدعي ترشيد قراراته الاستثمارية.
Small enterprises are currently important in the crisis period in Syria for their role in the local economy and covering the market with locally manufactured goods. Small enterprises are one of the main sources of income and contribute to improve the economic and social situation of a large segment of the Syrian population. The failure of these projects and their insolvency have significant impact on different sectors, the most important of which is the banking sector. The research aims to study the insolvency of small enterprises in the Syrian crisis and its impact on banking performance in Syria. The research also aims to provide the proposed solutions to finance loans for small enterprises in the period of reconstruction. The research is mainly based on an analytical descriptive approach that is based on describing the phenomenon of the failure of small enterprises. This research is a field study on three Syrian government banks. The study found that microfinance loans in banks have stopped altogether because of the crisis and the debt defaults of borrowers. The amount of interest and delay penalties for loans exceeded the value of the defaulted loan by about 40% of its amount. The profitability ratios in these banks were clearly affected by the Syrian crisis on the one hand, and the unpaid loans in 2011 were very large on the other hand. That financial analysis requires decisive decisions that the granting of such loans in government banks and reducing the risk of the security of these banks, contribute to the reconstruction phase. The study figured out important results that the government banks play a role in the formation of investment policies and in employment in these enterprises and also in their investment decisions.
Keywords: الأداء المالي -- الاقتصاد السوري -- التنمية المستدامة -- المشاريع التنموية